Comparison between BS 5950: Part 1: 2000 and Eurocode 3 for design the restrained structural steel beam - Swarna Mugil Pione Hirol (School of Environmental Engineering, University Malaysia Perlis, 2013)
This study is conducted to design and analysis the simply supported restrained steel beam by using Eurocode 3 (EC3) and BS 5950: Part 1: 2000 for comparing purposes.